Springer handbook of medical technology - Kramme, Rüdiger Kramme; Hoffmann, Klaus-Peter; Pozos, Robert S (Heidelberg New York Springer, 2011)
This concise, user-oriented and up-to-date desk reference offers a broad introduction to the fascinating world of medical technology, fully considering today?s progress and further development in all relevant fields. The Springer Handbook of Medical Technology is a systemized and well-structured guideline which distinguishes itself through simplification and condensation of complex facts. This book is an indispensable resource for professionals working directly or indirectly with medical systems and appliances every day. It is also meant for graduate and post graduate students in hospital management, medical engineering, and medical physics.
Part A Medical Technology Basics -- Part B Functional Diagnostics Devices -- Part C Medical Imaging -- Part D Therapeutic Devices -- Part E Monitoring -- Part F Medical Information Processing and Communication -- Part G Equipment and ToolsAppendices -- About the Authors -- Subject Index.
Electronic reproduction.
Keywords: Medical technology -- Handbooks, manuals, etc